2010
DOI: 10.1097/mao.0b013e3181e8fb1a
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effect on the Ocular Vestibular-Evoked Myogenic Potentials

Abstract: Aging effect (> 60 years old) on the oVEMPs includes reduced response rate, prolonged nI and pI latencies, and decreased nI-pI amplitude. Thus, age factor should be taken into consideration when interpreting the oVEMP results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 17 publications
9
45
3
1
Order By: Relevance
“…Those with nI latency > 12.9 ms (mean + 2SD) were interpreted as delayed responses, probably due to incomplete maturation of the otolithicocular reflex. For adults aged >60 years old, prolonged latencies and decreased amplitude of oVEMPs can be observed [64].…”
Section: Ovemps In Children Aged 3-14 Years Oldmentioning
confidence: 99%
“…Those with nI latency > 12.9 ms (mean + 2SD) were interpreted as delayed responses, probably due to incomplete maturation of the otolithicocular reflex. For adults aged >60 years old, prolonged latencies and decreased amplitude of oVEMPs can be observed [64].…”
Section: Ovemps In Children Aged 3-14 Years Oldmentioning
confidence: 99%
“…Previously, we had reported that all healthy subjects in age groups of 20-29, 30-39, 40-49, and 50-59 years exhibited 100% response rates of present oVEMPs elicited by BCV stimuli [Tseng et al, 2010]. In this study, a control group from healthy subjects with age and sex matched to the MD group also showed 100% present Fpz oVEMPs and present Fz oVEMPs (Table 1).…”
Section: Effects Of Age and Gender On Ovempsmentioning
confidence: 66%
“…The reason probably is because many patients were elderly (>65 years old) who had deteriorated VEMP responses due to the aging process [27]. Nevertheless, no significant difference existed in the percentages of abnormal oVEMP/cVEMP responses before and after treatment (p > 0.05; table 2).…”
Section: Discussionmentioning
confidence: 95%